PCR utility over conventional tests for detection of Mycobacterium spp. in patients with mastitis and granulomatous lymphadenitis: Case series - José J. Márquez-Barajas (Permanyer, 2021)
Objective: The present study aims to highlight the utility of quantitative polymerase chain reaction (qPCR) as a method for identifying typical and atypical mycobacterial infections in patients with mastitis and granulomatous lymphadenitis. Materials and methods: A total of five patients initially diagnosed with mastitis or granulomatous lymphadenitis based on their clinical characteristics in whom conventional tests were used as a diagnostic method were selected. Conclusion: The present study showed that the routine performance of qPCR for typical and atypical mycobacteria allows for improved diagnosis.